The Drosophila Dicer-1 Partner Loquacious Enhances miRNA Processing from Hairpins with Unstable Structures at the Dicing Site - Mandy Yu Theng Lim; Alvin Wei Tian Ng; Yuting Chou; Teck Por Lim; Amanda Simcox; Greg Tucker-Kellogg; Katsutomo Okamura (Cell Reports, 2016)
In Drosophila, Dicer-1 binds Loquacious-PB (Loqs-PB) as its major co-factor. Previous analyses indicated that loqs mutants only partially impede miRNA processing, but the activity of minor isoforms or maternally deposited Loqs was not eliminated in these studies. We addressed this by generating a cell line from loqs-null embryos and found that only ∼40% of miRNAs showed clear Loqs dependence. Genome-wide comparison of the hairpin structure and Loqs dependence suggested that Loqs substrates are influenced by base-pairing status at the dicing site. Artificial alteration of base-pairing stability at this position in model miRNA hairpins resulted in predicted changes in Loqs dependence, providing evidence for this hypothesis. Finally, we found that evolutionarily young miRNA genes tended to be Loqs dependent. We propose that Loqs may have roles in assisting the de novo emergence of miRNA genes by facilitating dicing of suboptimal hairpin substrates.